ANALYSIS OF THE PROCESS OF SOCIAL ADAPTATION AND CLINICAL DYNAMICS OF PATIENTS WITH INTELLECTUAL DISABILITY - Shodiyeva Feruza Beshimovna (World Scientific Research Journal, 2025)
Annotation. The article analyzed the process of social adaptation and clinical dynamics of 42 patients diagnosed with intellectual disability. During the study, the psychological, social, and clinical state of patients was assessed, and the level and dynamics of their adaptation were determined. Also, the effectiveness of therapy and rehabilitation methods was assessed, and recommendations aimed at increasing social integration were developed. The obtained results will contribute to the development of approaches aimed at improving the quality of life of patients with intellectual disabilities and optimizing their integration into society.